A new method for reducing VOCs formation during crude oil loading process - Karbasian, Hamid Reza; Kim, Dae Yeon; Yoon, Sang Youl; Ahn, Joo Ha; Kim, Kyung Chun (Journal of mechanical science and technology, 2017)
This study investigates the process of loading crude oil onto a tanker and the associated formation of Volatile organic compounds (VOCs). The main goal is to find mechanisms for reducing the amount of VOCs formation during the loading process. Different cases with a combination of a swirl unit and a U-bend were examined. Computational fluid dynamics (CFD) method was used to simulate the cavitation phenomenon, fluid flow pattern, and VOCs formation inside a loading pipeline. An experimental study was also done to investigate the accuracy of the numerical approach and to test the designed swirl units. Based on the numerical and experimental studies, a new approach is presented to reduce the VOCs formation notably during the loading process. The proposed approach can reduce the amount of VOCs formation by around 90 %, which can help to reduce the amount of wasted crude oil and also protect the atmosphere from gas emissions.